The impact of demographic and clinical characteristics on diabetic painful neuropathy - Assunção António; Campos Dina; Marques Rui; Cunha Inês; Santos Patrícia; Martins Adriana; Gonçalves Ana Sofia; Rebelo Ana; Lima Carolina; Matos César; Prata Ana Cristina; Teixeira José Tiago; et al. (Sciendo, 2020)
Introduction. Diabetic neuropathy (DN) is one of the most devastating complications of diabetes mellitus; however, in contrast to other countries, there are no scientific studies in Portugal evaluating the impact of demographic and clinical characteristics of this pathological entity. The aim of this study was to evaluate the impact of gender, metabolic control, age of diabetic patients, as well as time of disease progression, the appearance of complaints related to neuropathic pain.